Optimalisasi Peran Pengawas Dalam Meningkatkan Mutu Pendidikan Yang Berkemajuan - Nurhuda, Ahmad; Muhammad Yusuf Rinjani; Muhammad Nur Rahmat (Al-Abshar: Journal of Islamic Education Management, 2024)
Education is a dynamic thing. Likewise in terms of quality. Quality of education is the main standard in providing quality education. The quality of education does not only talk about the results, but also the process of education itself. Education must be able to transform according to the challenges and developments of the times, adapt to developments in science and technology and be accepted by society because it has an impact on social reality. Achieving good quality education is supported by a quality assurance system implemented by each educational unit. Supervisors of educational units or schools have a very important role in improving the quality of education. This article aims to conduct a review of optimizing the role of supervisors in improving the quality of progressive education. To study this, the author uses a qualitative approach with the type of library research or literature study. Through this article, it is hoped that school supervisors can carry out their role in efforts to improve the quality of progressive education, namely education that can answer the challenges of the times and have an impact on social reality.